Electrocardiographic alterations associated with heart transplantation. Triggers, mechanisms and meaning (2017)
Introduction: Heart rhythm disorders are associated with increased morbidity and mortality. However, triggers and implications in patients with heart transplantation are not clear.Objectives: The purpose of this research paper is to identify and explain the determinants for the onset of electrical conductivity alterations in patients with a heart transplant, as well as to describe the most common arrhythmias and their pathological implications.Materials and methods: A literature review was made in the PubMed online database for a total of 411 results. In addition, clinical practice guidelines on cardiac transplantation, cardiovascular electrophysiology and infective endocarditis were searched. Sixty articles related to the objectives of this study were chosen.Results: Surgical technique, heart denervation, sinus node trauma, graft rejection, endomyocardial biopsies and infections are the main factors that compromise organ viability and the life of transplanted patients. These factors can be observed as sinus rhythm disturbances.Conclusions: When a cardiac arrhythmia is detected, the medical team must provide a treatment that is not limited to symptomatic and sinus rhythm control. An active search of the etiology must be initiated since it may indicate an underlying pathological process.